“. . . one part life and nine parts the other thing”: Painters and the Stage - Botelho, Teresa (Hungarian Journal of English and American Studies, 2020)
Bringing the act of artistic creation to the stage involves a multiplicity of strategies and interrogations that are not easily contained within the boundaries of the “drama of the artist” as understood in its quasi-biographical sense. This is especially true of visual art which cannot be represented by words only but requires a different kind of presence on stage. In many Künstlerdramas the biographical presence tends to impose recognizable limits to the fictionalization exercise, which frequently turns to the individual creator as the center of an inquiry into the problematics of artistry. This paper discusses how two contemporary Künstlerdramas, John Logan’s Red (2009) and John Murrell’s The Far Away Nearby (1996), attempt to reinvent the trope by weaving the biographical record with the performative presence of acts of staged visuality that re-center the act of artistic creation. (TB)